cis,trans,cis-1,2,3,4-Tetrakis[2-(ethylsulfanyl)phenyl]cyclobutane - Barbara Sohr; Florian Glöcklhofer; Berthold Stöger; Matthias Weil; Johannes Fröhlich (IUCrData, 2016)
The title cyclobutane derivative, C36H40S4, formed serendipitously through a photochemically initiated [2 + 2] cycloaddition. The asymmetric unit contains half a molecule with the 2-(ethylsulfanyl)phenyl substituents in a cis configuration, the other half of the molecule being generated by the application of a twofold rotation operation. The substituents in both halves of the molecules are in a trans arrangement relative to each other. The cyclobutane ring shows angular and torsional strains, with C—C—C bond angles of 89.80 (8) and 88.40 (8)°, and an average absolute torsion angle of 14.28 (10)°. The angle of pucker in the ring is 20.27 (12)°. The Ccb—Ccb—Cb angles between the cyclobutane (cb) ring atoms and the attached benzene (b) ring atoms are widened and range from 115.19 (10) to 121.66 (10)°. A weak intramolecular C—H...S hydrogen-bonding interaction between one of the cyclobutane ring H atoms and the S atom may help to establish the molecular conformation. No specific intermolecular interactions are found.